Constant Current Coulometric Determination of Some Phenothiazine Drugs in Pharmaceutical Preparations - B. Patil, Dilip; M. Chafle, Dilip (Asian Journal of Chemistry, 2010)
A rapid amperostat-coulometric method has been described for the microgram level determination of some phenothiazine derivatives in pharmaceutical preparations. The method is based on estimation of these derivatives by determining the amount of electro- lytically generated bromine required to react stoichiometrically with these drugs present in the solution. In case of each drug progressively smaller quantities are estimated and minimum quantity that can be estimated with reasonable accuracy is determined. Further, a systematic error analysis in the estimation of these derivatives by this method is also carried out.